A study on temperature spatial distribution of a greenhouse under solar load with considering crop transpiration and optical effects. (15th February 2022) - Xu, Ke; Guo, Xuan; He, Junming; Yu, Bin; Tan, Jinglu; Guo, Ya
Highlights: A temperature spatial distribution model for a greenhouse was developed. Crop transpiration and optical effects on the temperature distribution was considered. Crop transpiration and optical effects have high impact on the temperature distribution. Abstract: Spatial temperature distribution of a greenhouse is critical to precision agriculture management, especially for the vertical cultivation mode. Crop transpiration and optical effects influence spatial temperature distribution of a greenhouse, which, however, were often omitted in literature. In this work, a Computational Fluid Dynamics model on studying spatial temperature distribution of a greenhouse was developed with considering the effects of air (light absorption), crop (light absorption, reflection, transmission, and transpiration), and soil (light absorption and heat radiation) in the greenhouse under dynamic solar load based on the law of energy conservation. A set of field tests was used to validate the developed Computational Fluid Dynamics model. Spatial temperature distributions of the greenhouse under different scenarios were simulated with and without considering crop effects. The results show that the temperature standard deviation of the greenhouse with considering the crop effects was about 31.68% higher than that without considering the crop effects. This implies that greenhouse temperature distribution is significantly influenced by crop transpiration and optical effects. The results also show that the highest temperature appears in the air region below the top of greenhouse and changes with the dynamic solar radiation direction, and the temperature may vary by about 63.65% during the day. There is a temperature difference of 2 °C-3 °C at the same height level between the greenhouse with and without considering the crop effects. This work is important for understanding the non-uniform temperature spatial distribution pattern of a greenhouse as affected by crops, and provides information for sensor deployment, monitoring, and control of greenhouse temperature.